Risk Analysis of Vapour Cloud Explosions for Oil and Gas Facilities - Ma, Guowei; Huang, Yimiao; Li, Jingde (Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on describing and applying risk analysis of vapour cloud explosions (VCEs) in various oil and gas facilities, such as petrol stations, processing plants, and offshore platforms. Discussing most of the complicated features of gas explosion accidents, the book studies in detail the gas explosion risk analysis approaches of different oil and gas facilities in order to develop more accurate, detailed, efficient and reliable risk analysis methods for VCEs under different conditions. Moreover, it introduces an advanced overpressure approach to predict VCEs using computational fluid dynamics (CFD) modelling, and details applications of CFD using a FLame ACceleration Simulator (FLACS). The book is intended for researchers and organisations engaged in risk and safety assessments of VCEs in the oil and gas industry.